Geographical distribution and niche conservatism in populations of Orthogeomys dariensis (Rodentia: Geomyidae) in the Chocó Biogeographical region - Valencia-Mazo, Juan David; Solari, Sergio; Arias-Alzate, Andres (THERYA, 2017)
The Chocó biogeographic region is among the richest in terms of natural resources, species richness and number of endemisms. Among the species endemic to this region, the pocket gopher, Orthogeomys dariensis (Geomyidae), presents a disjunct distribution on both sides of Serranía Darien-Baudó. These populations have been considered as different species, under the names O. dariensis s.s. (northern) and O. thaeleri (southérn). This study aims to model the potential distribution of O. dariensis s.s. to assess niche divergence between these geographic populations. Using presence records, associated data, and 19 bioclimatic variables, an ecological niche-modeling approach was applied to: 1) estimate the distribution of the northern and southern populations, both separately and as a single species; 2) assess whether each population model predicts the distribution of the other, and analyze their differences through a MESS analysis; and 3) test the overlap and similarity of these niches as a proxy for niche conservatism between O. dariensis s.s. and O. thaeleri, through the estimation of ecological niche ellipsoids for the fundamental niche (EA). When considered as separate populations, these show an allopatric distribution, with the Darién-Baudó zone acting as a barrier between them. Also, O. dariensis data predicts a large part of the distribution of O. thaeleri over the study region, and vice versa. When considered as a single species, it shows a broader and continuous range, including the Darién-Baudó region as part of its potential distribution. The MESS analysis shows similar climatic conditions in general, and few particular conditions that are unique to each zone, which would not represent conditions so unique as to segregate them. Therefore, the apparent disjunction between populations may be due to the lack of records and systematic surveys in this region. This is also reflected in the moderate overlap of their niche ellipsoids, showing the ecological conditions shared between these populations. Our results support the existence of a single species, O. dariensis (sensu Hafner 2015), with a broad and continuous distribution in the Chocó biogeographic region. This is consistent with recent analyzes of DNA data showing very low genetic divergence between populations north and south of Darién-Baudó (as an intermediate area). Rather than a barrier promoting diversification, this region could represent a dispersal area for these populations.